TEACHING ENGLISH IN PRIMARY CLASSES - Obidova , Iroda Ravshan qizi (Educational Research in Universal Sciences, 2023)
This article discusses various ways of teaching English in primary classes. It emphasizes the importance of creating a positive and engaging learning environment, incorporating interactive activities, and using visual aids and technology to enhance learning. The article also suggests strategies for teaching grammar, vocabulary, and pronunciation, as well as promoting reading and writing skills. Additionally, it highlights the benefits of integrating cultural aspects into language learning and fostering a communicative approach to language teaching.